Gbb/BMP signaling is required to maintain energy homeostasis in Drosophila. - Ballard, S.L.; Jarolimova, J.; Wharton, K.A. (Developmental Biology, 2010)
The coordination of animal growth and development requires adequate nutrients. During times of insufficient food, developmental progression is slowed and stored energy is utilized to ensure that cell and tissue survival are maintained. Here, we report our finding that the Gbb/BMP signaling pathway, known to play an important role in many developmental processes in both vertebrates and invertebrates, is critical in the Drosophila larval fat body for regulating energy homeostasis. Animals with mutations in the Drosophila BMP-5,7 orthologue, glass bottom boat (gbb), or in its signaling components, display phenotypes similar to nutrient-deprived and Tor mutant larvae. These phenotypes include a developmental delay with reduced overall growth, a transparent appearance, and altered total lipid, glucose and trehalose levels. We find that Gbb/BMP signaling is required in the larval fat body for maintaining proper metabolism, yet interestingly, following nutrient deprivation larvae in turn show a loss of BMP signaling in fat body cells indicating that Gbb/BMP signaling is a central player in homeostasis. Finally, despite strong phenotypic similarities between nutrient-compromised animals and gbb mutants, distinct differences are observed in the expression of a group of starvation responsive genes. Overall, our results implicate Gbb/BMP signaling as a new pathway critical for positive regulation of nutrient storage and energy homeostasis during development.